1985
DOI: 10.1055/s-2007-1007043
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Alterations in Muscle Transfers with Microneurovascular Anastomoses

Abstract: The time course of alterations in muscle transfers with microneurovascular anastomoses was studied in 17 rabbits. The left rectus femoris muscle was transferred to the right side. For comparison, in some animals the right rectus femoris muscle was transferred from the right to the left side, but without vascular repair. Two, seven, 14, 21, and 30 days after transfer, the electric excitability, macroscopic appearance, histology, histochemistry, ultrastructure, and activity of muscle enzymes were assessed. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Frey has shown that the early denervation and subsequent reinnervation is associated with marked histochemical changes in the first 3 months posttransfer in the rabbit model. 32 Stevanovic et al9 noted focal areas of necrosis comprising about 10-20% of the total area in a dog sartorius model at 3 months of recovery. They speculate that a longer recovery period would be associated with a more normal histochemical appearance.…”
Section: Discussionmentioning
confidence: 97%
“…Frey has shown that the early denervation and subsequent reinnervation is associated with marked histochemical changes in the first 3 months posttransfer in the rabbit model. 32 Stevanovic et al9 noted focal areas of necrosis comprising about 10-20% of the total area in a dog sartorius model at 3 months of recovery. They speculate that a longer recovery period would be associated with a more normal histochemical appearance.…”
Section: Discussionmentioning
confidence: 97%
“…17 (c) In free functioning muscle transfers in cases of facial reanimation, the transplants can lead to clinically sufficient results, although the number of reinnervating motor nerve fibers is limited to 20 percent in cross-face nerve transplants. 2,18,19 (d) A selective enlargement of motor units is possible, when muscle fibers are additionally recruited by adjacent motor end plates. (e) Finally, the question arises whether or not a large muscle mass could be a stimulus for nerve sprouting.…”
Section: Discussionmentioning
confidence: 99%
“…After the regenerating nerve fibers controlling the function of smiling had grown to the end of the sural nerve graft, free transplantation of the gracilis muscle with microneurovascular anastomoses was performed in a second procedure 10 months later. [12][13][14] In adults dissatisfied with their degree of insufficient eye closure, we used a combination of transposition of the central portion of the temporal muscle to the upper and the lower eyelids to rapidly restore this essential function and thus protect the cornea.…”
Section: Surgical Proceduresmentioning
confidence: 99%